PENGARUH JENIS KEMASAN DAN LAMA PENYIMPANAN TERHADAP SIFAT KIMIA, MIKROBIOLOGI DAN ORGANOLEPTIK PERMEN KARAMEL SUSU KAMBING - Susilawati Suslawati; Putri Cyntia Dewi (Jurnal Teknologi & Industri Hasil Pertanian, 2011)
Caramel candy is a kind of toffee classified into  soft candies, and  processed using milk and sugar as the main ingredients. One way to prevent food spoilage is to use suitable packaging as well as storage system. This study was aimed to determine the effects of  packaging materials and storage time until 28 days at room temperature  and their interaction effects on the the chemical, microbiological, and organoleptic properties , and its accordance with SNI 3457.2 caramel candy standard. The study was conducted in two groups of factors and arranged in Complete Randomized Design with three replications. The first factor was the type of packaging (P) consisted of polyethylene plastic (P1), aluminum foil (P2), and oil paper packaging (P3). The second factor was the duration of storage (L) consisted of 0 days (L1), 7 days (L2), 14 days (L3), 21 days (L4), and 28 days (L5).  The homogenity and additivity  of  the data were tested using Barlett  and Tuckey tests, continued using ANOVA ,  and then further tested using  comparison and orthogonal polynomials at of 1% or 5% level of significance.  The results showed the samples wrapped in aluminum foil  and stored for 28 days at room temperature, was found to be the best type of packaging. The criteria of the best goat’s milk caramel candies were:  water content of 5,81% w/w, ash content of 0,95% w/w, reducing sugar content 2,26% w/w, total molds and yeasts 0,49x102 colonies/gram, a total microbial of 2,83 colonies/gram, and the color, texture, taste, and aroma were brown, soft, sweet, and neutral. these criteria met the SNI 3547.2 (2008) quality standard for  caramel candies.